MODERN INFORMATION AND COMMUNICATION TECHNOLOGIES AND OPPORTUNITIES FOR THEIR USE IN THE EDUCATIONAL PROCESS - Tilavova, Turdixol (Физико-технологического образование, 2024)
In this work we discuss the information and communication technologies (ICT) in the educational processes. Innovative pedagogical processes create the basis not only for the competitiveness of any educational services market, but also for the intensive development of the personality of a teacher and a student, the democratization of interaction and communication between a teacher and a student, the humanization of the educational process, the orientation of students to active learning and self-education, the modernization of educational technologies and, as well as the material and technical base of education, the professionalism of teachers, their creativity determines the direction of development of their searches, plays an important role in the development of students as individuals. Multimedia is the ability to work with different forms of information on a computer: color graphics, dynamic effects in text and graphics, sound output and synthesized music, animation, as well as full-length video clips and videos. Multimedia is a modern computer information technology that allows you to combine text, sound, video, graphics and animation into a single computer system